A model for the thin film friction factor in near-horizontal stratified-annular transition two-phase low liquid loading flow. (May 2018) - Rodrigues, Hendy T.; Pereyra, Eduardo; Sarica, Cem
Highlights: A model for the gas friction factor increase due to the thin liquid film is proposed. Model based on liquid mass balance, droplet atomization and deposition. Modified equation for the rate of droplets atomization at high pressure systems. Comparison with available data obtained in large diameter and high pressure systems. Abstract: For relatively large diameter pipes and at high gas flow rates, low-liquid loading near-horizontal two-phase flows presents a thin liquid film flowing at the upper part of the pipe wall while a stratified liquid film is observed at the bottom. This paper presents a new model that takes the thin film into account for pressure gradient calculations. The model evaluates the thin film thickness based on the Nusselt falling film theory coupled with a liquid mass balance in the cross sectional area of the pipe. This coupling relates the rate of deposited droplets at the thin film with the atomization and deposition at the bottom liquid film. The thin film thickness is used in an equation that corrects the gas-wall friction factor. The model is evaluated against existing data acquired at larger diameters and higher pressures improving the pressure gradient prediction at higher gas flow rates.